ASSESSMENT OF WORK POSTURES ON NON-MECHANICAL RICE HARVESTING (CASE STUDIES IN BANTUL AND SLEMAN DISTRICTS, DIY PROVINCE) - Guntarti Tatik Mulyati; Muhammad Maksum; Bambang Purwantana; Makhmudun Ainuri (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2020)
Rice harvesting is a high ergonomic risk due to the working position, an awkward posture, and the repetition activity. Rice harvesting causes body pain in the part of low back, hand, and wrist. This study aims to (1) identify the characteristics of non-mechanical rice harvesting; (2) determine the working posture of rice harvesters using the Ovako Working Assessment System (OWAS) method, Quick Exposure Checklist (QEC), Rapid Entire Body Assessment (REBA), Postural Ergonomics Risk Assessment (PERA); and (3) determine the best method to assess harvesters work posture. An observation was conducted to nine of healthy workers in Bantul and Sleman districts, Daerah Istimewa Yogyakarta (DIY) province. The questionnaire was set to collect respondent demographics data. Data for harvester body posture (neck, trunk, leg, wrist, lifting load, shoulder) repetition, duration and force were collected by observation in the field. A sickle was used to cut rice straw, while a manual gepyok and mobile hand thresher was used to threshing rice panicles. Four methods were applied to assess the work posture, i.e., OWAS, QEC, REBA, PERA methods. Based on observation, five workstations were identified: (1) cutting rice straw, (2) transporting rice straw, (3) threshing of panicles, (4) sorting, and (5) packaging and transporting. REBA and PERA showed a similar trend of the ergonomic risk, high to low risk took place in workstation transporting rice straw, packaging and transporting, cutting, and threshing. The assessment of work posture that is most suitable for non-mechanical harvesting methods was the REBA method with an accuracy of 92.9%.